1981
DOI: 10.1002/app.1981.070260701
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics of polyacrylamide and sulfonate‐containing polyacrylamide copolymers on sodium kaolinite

Abstract: SynopsisPolyacrylamide and its copolymer containing 6.8 mole % 2-acrylamido-2-methylpropane sulfonic acid were prepared by an irradiation-initiated precipitation polymerization technique. The polymer was characterized by intrinsic viscosity under conditions similar to those used during adsorption measurements. Hydrolytic degradation of the polyacrylamide was found to be negligible under conditions used. The adsorption substrate, sodium kaolinite, was prepared by extensive ion exchange treatment. Equilibrium ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 31 publications
(4 reference statements)
1
20
1
Order By: Relevance
“…Indeed, coagulation (induced by salt effects) and flocculation (occuring through polymer particle bridging) give rise to a reduction in the area available for polymer adsorption [7]. It has been reported elsewhere that the concentration of electrolyte has no effect on the adsorption of polyacrylamide on Na-kaolinite [16]. The above arguments may explain the discrepancies between our results and others obtained using very concentrated clay suspensions.…”
Section: Effect Of the Electrolyte Concentration On Polymer Adsorptioncontrasting
confidence: 62%
“…Indeed, coagulation (induced by salt effects) and flocculation (occuring through polymer particle bridging) give rise to a reduction in the area available for polymer adsorption [7]. It has been reported elsewhere that the concentration of electrolyte has no effect on the adsorption of polyacrylamide on Na-kaolinite [16]. The above arguments may explain the discrepancies between our results and others obtained using very concentrated clay suspensions.…”
Section: Effect Of the Electrolyte Concentration On Polymer Adsorptioncontrasting
confidence: 62%
“…Adsorption of PAM on soil and clay mineral surfaces has been demonstrated to be rapid and irreversible in several studies although the degree of adsorption is dependent on PAM conformation, soil or mineral properties, and soil solution characteristics (Hollander et al, 1981;Nabzar et al, 1984Nabzar et al, , 1988Nadler et al, 1992;Pradip and Fuerstnau, 1980;Tanaka et al, 1990). Because of its high affinity for clay mineral surfaces in soil, PAM becomes concentrated in the upper portions of soil profiles to which it is applied in irrigation water.…”
Section: Pam Properties Affecting Efficacymentioning
confidence: 99%
“…Polymer and surfactant are either positive or negative; hence, binding of SLES to SPAM is prevented by the strong electrostatic repulsion between the anionic groups of the polymer and the polar heads of the surfactant molecules. Changes in the conformation of the polymer chains in the presence of anionic surfactant caused by screening of the electrostatic repulsion between groups of polymer charged by the counter-ions of the surfactant species produced significant changes in polymer adsorption [15,32]. Both SPAM and SLES molecules can adsorb onto the surface of carbonate rock particles.…”
Section: Effect Of Presence Of Anionic Surfactantmentioning
confidence: 99%
“…The effects of other variables on adsorption have also been studied. Hollander et al [15] studied the adsorption of sulfonated polyacrylamides (SPAM) onto kaolinite at different pH values, ionic strengths and temperatures. They concluded that the adsorption of the polymer increased as the ionic strength increased but decreased as the pH decreased and that adsorption was independent of temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation